Tracking the Traces of Success: The Effect of Halal Awareness and e-WOM in Building Consumer Loyalty - Desty Prawatiningsih; Siti Yuli Yani; Lala Nabilah Candra (Jurnal Economic Resource, 2026)
This study examines the influence of Halal Awareness and Electronic Word of Mouth (e-WOM) on consumer loyalty among the Millennial Generation in Indonesia. Using a quantitative approach, the research involves a population of millennials residing in Serang City, Banten. Data were collected from 268 respondents through an online questionnaire and analyzed using multiple linear regression to identify the effects of Halal Awareness and e-WOM on consumer loyalty, both partially and simultaneously. The analysis results indicate that both variables significantly influence consumer loyalty. Halal Awareness enhances loyalty by fostering trust and positive perceptions of halal products, while e-WOM strengthens consumer engagement through authentic and relevant digital recommendations. These findings underscore the importance of communication strategies that focus on halal values and e-WOM to build consumer loyalty in an increasingly competitive market. This study suggests that companies can optimize halal communication, integrated with e-WOM strategies, to strengthen their relationships with Millennial consumers.